2009
DOI: 10.1080/09670260802419481
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and digalactosyldiacylglycerol composition of dinoflagellates. I. Peridinin-containing taxa

Abstract: Two glycolipids, monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG), are components of chloroplast membranes. This study addresses the lack of information regarding the major intact forms of these glycolipids in photosynthetic dinoflagellates through the use of a full-scan positive-ion electrospray ionization/mass spectrometry (ESI/ MS) survey of MGDG and DGDG in 35 peridinin-containing taxa from the class Dinophyceae. Further analysis using positive-ion electrospray ionization/mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(114 citation statements)
references
References 19 publications
5
108
0
Order By: Relevance
“…We make a similar hypothesis for the presence of 20:5 at the sn-1 position of the major forms of MGDG and DGDG in the Cluster 2 dinoflagellates identified by Gray et al (2009): that this trait has been obtained from its red algal plastid ancestor. However, with the exception of radiolabelling studies by Khozin et al (1997) and Sato & Moriyama (2007), little is known about the genes that encode the enzymes involved in the synthesis of galactolipids in the potential red algal ancestors of the plastids of C. velia and peridinin-containing dinoflagellates.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We make a similar hypothesis for the presence of 20:5 at the sn-1 position of the major forms of MGDG and DGDG in the Cluster 2 dinoflagellates identified by Gray et al (2009): that this trait has been obtained from its red algal plastid ancestor. However, with the exception of radiolabelling studies by Khozin et al (1997) and Sato & Moriyama (2007), little is known about the genes that encode the enzymes involved in the synthesis of galactolipids in the potential red algal ancestors of the plastids of C. velia and peridinin-containing dinoflagellates.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the presence of 20:5 at the sn-2 position to form 20:5/20:5 MGDG and 20:5/20:5 DGDG was found to be very rare in peridinin-containing dinoflagellates, with only a few organisms possessing either lipid and only at relative abundances of less than 10% of the total galactolipids (Gray et al, 2009). Rather, in both of the clusters of peridinin-containing dinoflagellates identified by Gray et al (2009), it was observed that either 18:5 or 18:4 was present at the sn-2 position in the most abundant forms of MGDG and DGDG. In contrast, C. velia possessed 20:5, but neither 18:5 nor 18:4, at the sn-2 position.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations